Endothelial cell adhesion molecule CD146: implications for its role in the pathogenesis of COPD. Issue 4 (9th July 2013) - Kratzer, Adelheid; Chu, Hong Wei; Salys, Jonas; Moumen, Zakaria; Leberl, Maike; Bowler, Russ; Cool, Carlyne; Zamora, Martin; Taraseviciene‐Stewart, Laima
Abstract CD146 is an adhesion molecule localized at endothelial cell junctions and facilitates cell–cell interactions. The circulating soluble form (sCD146) lacks both the intracellular and the transmembrane domains. In this study we show that CD146 expression was significantly decreased in the lung tissue of smokers with chronic obstructive pulmonary disease (COPD) and also in rats exposed to second‐hand smoke (SHS). Concurrently, levels of sCD146 were increased in both the plasma and bronchoalveolar lavage fluid (BALF) of COPD patients as well as in BALF from rats exposed to SHS. Decreased or abolished CD146 protein expression in rat pulmonary micro‐ and macrovascular endothelial cells was found after treatment with cigarette smoke extract (CSE), proinflammatory cytokine interleukin 18 (IL‐18) or after silencing CD146 expression with siRNA. The decrease in CD146 protein was accompanied by increased endothelial monolayer permeability and enhanced macrophage infiltration in vitro. In CD146 knockout (KO) mice, distinct perivascular oedema was seen and increased numbers of inflammatory cells, along with increased protein levels in BALF. Increased sCD146 was found in BALF and plasma from patients with COPD. The circulating plasma levels of sCD146 correlated positively with the presence of anti‐endothelial cell antibodies (AECAs). sCD146 in combination with AECAs may be useful markers for early detection of COPD. Our study indicates that loss of CD146 function damages pulmonary endothelial integrity. This damage may represent part of the pathophysiological processes that are involved in the basic aetiology of COPD/emphysema. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.